Triple-Mode Grid-Balancing Plants via Biomass Gasification and Reversible Solid-Oxide Cell Stack: Economic Feasibility Evaluation via Plant Capital-Cost Target - Zhang, Yumeng; Wang, Ningling; Li, Chengzhou; Pérez-Fortes, Mar; Duan, Liqiang; Van herle, Jan; Maréchal, François; Lin, Tzu-En; Wang, Ligang; Yang, Yongping (Frontiers in Energy Research, 2021)
Electricity production and consumption must be balanced for the electrical grid. However, the rapidly growing intermittent power sources are now challenging the supply-demand balance, leading to large flexibility needs for grid management. The plant integrating biomass gasification and reversible solid-oxide cell stacks can be potential flexibility means, which could flexibly switch among power generation, power storage and power neutral modes. This paper investigates the economic feasibility of such grid-balancing plants, i.e., plant CAPEX target, via a systematic overall decomposition-based methodology for real geographical zones and flexibility-need scenarios. The plant CAPEX target (€/ref-stack) is defined as the maximum affordable investment cost for each reference stack (active cell area 5120 cm2